Optimizing sucrose and BAP concentrations for in vitro microrhizome induction of Zingiber officinale Rosc. ‘Tambunan’ - Devina David,; Ling, Ee Chuwan; Jualang Azlan Gansau, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In vitro microrhizome induction is considered as an effective tool for high yielding rhizomatous crops. In this study, the effect of sucrose and BAP was examined to establish a suitable protocol for in vitro microrhizome production of Zingiber officinale Rosc. ‘Tambunan’. The in vitro derived plantlets were used as explants and cultured on Murashige and Skoog (MS) medium treated with a combination of sucrose and BAP at various concentrations and maintained at 25 ± 2°C with 16 hr of photoperiod. After three months of culture, explant responded well on MS medium supplemented with 60 g/L of sucrose and 6 mg/L of BAP compared to other treatments. This treatment had significantly promoted the highest number of microrhizomes (seven) with a total weight of 2.90 g and a total number of 35 buds. Acclimatization of this microrhizome showed 88% of survivability rate after 21 days with a formation of new shoot and root. The current finding revealed the potential of microrhizomes for large-scale production of healthy planting material to support the ginger industry in this region.